A Comment and Epilogue. (September 2015) - Howse, Rob
Abstract : The Appellate Body report in EC-Seal Products is a landmark decision in several respects: for its recognition that animal welfare is a matter of public morality that may justify a trade ban in response to cruelty; for the AB's new–found clarity with respect to the irrelevance of regulatory purpose in the determination of "treatment no less favourable" under the National Treatment and MFN provisions of the GATT; for its suggestion that trade measures not defined by product–related distinctions but other criteria are not covered by the TBT Agreement; and for its partial acknowledgement that a Member may maintain a measure consistent with Article XX even if the measure represents a complex trade–off between a main purpose and other purposes that may limit the extent the main purpose can be furthered. But the decision arguably raises as many questions as it answers, and some have already complained about the rather sphinx–like quality of the judgment.